Answering A Critique of Rational - Emotive Therapy - Ellis, Albert (Canadian Journal of Counselling and Psychotherapy, 2012)
Each of the major ideas presented by Morris in his article "The Rational-Emotive Approach: A Critique" are dealt with by Albert Ellisas he answers some thoughtful criticisms of R. E. T. Ellis counters Morris' major points and suggests in effect that experimental evidence is lacking in support of these various claims. Ellis further suggests thatan "existential" bias pervades and that this is quite different from hisown hard-headed brand of "existentialism". Chacune des idées principales éconcées par Morris dans son article"The Rational-Emotive Approach:ACritique" est discutée par Albert Ellis. Ellis refuteles principaux arguments de Morris et souligne l'absence d'évidence expérimentale qui appuierait les idées soulevées par Morris. De plus, Ellis suggère qu'un biais "existentialiste" s'infiltre dans l'article de Morris et que ce biais diffère de sa conception de l'existentialisme.